2012
DOI: 10.1038/ejcn.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Influences on infant feeding decisions of first-time mothers in five European countries

Abstract: Background/ Objectives: Infant feeding decisions made by new parents have significant health implications. The study aimed to investigate: influences on infant feeding decisions; characteristics of mothers reporting reliance on alternative information sources; associations between reliance on different sources and intentions to exclusively breastfeed and introduce complementary foods later, and subsequent breastfeeding and weaning behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
5
31
0
4
Order By: Relevance
“…The DoH adopted that recommendation in 2003, also stating that solid foods should never be given to babies under 17 weeks 1 2. Premature introduction of solid foods has long been a concern in the UK, and following the change in recommendations, the proportion of infants introduced to solid foods before 4 months of age dropped from 51% in 2005 to only 30% in 201018 and similar trends have also been reported in the USA9 and other European countries 19. Despite this, 43% of infant foods were labelled as being suitable ‘from age 4 months’ which, while compatible with the EC Directive that ‘the stated age shall not be less than 4 months for any product’,20 seems likely to offer encouragement to introduce complementary foods before 6 months.…”
Section: Discussionmentioning
confidence: 65%
“…The DoH adopted that recommendation in 2003, also stating that solid foods should never be given to babies under 17 weeks 1 2. Premature introduction of solid foods has long been a concern in the UK, and following the change in recommendations, the proportion of infants introduced to solid foods before 4 months of age dropped from 51% in 2005 to only 30% in 201018 and similar trends have also been reported in the USA9 and other European countries 19. Despite this, 43% of infant foods were labelled as being suitable ‘from age 4 months’ which, while compatible with the EC Directive that ‘the stated age shall not be less than 4 months for any product’,20 seems likely to offer encouragement to introduce complementary foods before 6 months.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies have shown that mothers from a disadvantaged background were less likely to use the Internet as a source of information for infant feeding [47]. A strength of our study was that approximately equal number of participants of both high and low educational background were recruited unlike other mHealth programs targeted at addressing infant feeding [48].…”
Section: Discussionmentioning
confidence: 99%
“…andChow, 2010, Johnson et al, 2013). A growing body of literature suggests that fathers play a vital role in their wives' breastfeeding decision and behaviors (Harwood, 2011;Bonia et al, 2013;Moore and Rempel, 2010;Swarts, Salome, Kruger and Robin, 2010;Solomon, 2010;Gage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%